Antifungal impact of volatile fractions of Peumus boldus and Lippia turbinata on Aspergillus section Flavi and residual levels of these oils in irradiated peanut - Passone, Maria Alejandra (2013)
To investigate the antifungal properties of essential oil (EO) vapors from boldo and poleo on Aspergillus section Flavi and the residual levels of the oils in peanut, irradiated peanuts conditioned at three water activities (0.98, 0.95, 0.93) were treated with 2 and 3 μL/g of boldo and 3 and 5 μL/g of poleo. EO treatments produced the greatest impact on fungal growth parameters, followed by oil concentrations and aW levels. The three main components in peanut exposed to oil vapors were piperitone oxide, α-terpinene and eucalyptol for boldo and β-caryophyllene epoxide, limonene and piperitenone for poleo. Residues of boldo and poleo EO were significantly decreased from 24.7 to 100% and from 26.6 to 99.7% at the end of the incubation period, respectively. The application of nontoxic boldo oil as fumigant in the control of Aspergillus section Flavi may represent a potential alternative antifungal treatment, without significant residues after 35 days.